PENGARUH DEWAN KOMISARIS, PROFITABILITAS, KEPEMILIKAN SAHAM PUBLIK DAN KEPEMILIKAN MANAJERIAL TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDO - Teguh Erawati; Hana Herlina (Fakultas Ekonomi UNIBBA, 2021)
This study aims to prove the effect of the board of commissioners, profitability, public share ownership and managerial ownership on corporate social responsibility disclosure. The nature of this research is quantitative. The population in this study are manufacturing companies in the consumer goods industry which are listed on the Indonesia Stock Exchange in 2015-2019 and there are 52 companies. The sampling technique used purposive sampling and obtained 9 companies. This study uses secondary data in the form of annual financial reports which are downloaded from www.idx.co.id. Data analysis used multiple linear regression analysis with the help of the SPSS 25 software program. The results showed that the board of commissioners and public share ownership had a positive and significant effect on corporate social responsibility disclosure. Meanwhile, profitability and managerial ownership do not have a significant effect on corporate social responsibility disclosure.